The feasibility of herbarium based local wisdom on plant structure and development subject - Mucharommah Sartika Ami; Anggi Indah Yuliana (STKIP Persada Khatulistiwa Sintang, 2021)
The development of herbarium based on local wisdom as a learning media for the subject of plant structure and development, especially traditional food, is still very rare. This is very unfortunate because local wisdom contains pedagogical values that play an important role in improving the quality of learning. This study aims to determine the feasibility of the herbarium developed according to the validation results of the instructional media expert and herbarium expert. The development model used is ADDIE and the stages carried out in this research are up to the development stage. The results showed that the herbarium based on local wisdom developed was suitable as a learning media for the subject of plant structure and development, with an average score of the validation results of the two validators was 81,25. Both validators suggest using plant specimens that display complete organs, consisting of roots, stems, leaves, flowers, fruits, and seeds in making herbariums.Keywords: Local wisdom, herbarium, learning media